Peningkatan kemampuan Siswa XII-A-1 SMAN-3 Atambua Berbicara Bahasa Inggris melalui Dialog berpasangan (Bilingual : Jurnal Pendidikan Bahasa Inggris, 2023)
Class XII-A-1 students of SMA Negeri 3 Atambua experience problems in learning English, especially in conversation or speaking English orally. This was shown by the condition of the class containing 24 students who could not respond well to the conversation proposed by the teacher, and the learning outcomes were relatively low. The purpose of this study was to improve the students' ability to speak English orally. The research method used is Classroom Action Research by applying two cycles. In the first cycle, dialogue was carried out orally in English between the teacher and students. Each student is invited by the teacher to dialogue through 5 questions for each student, and each student responds. The second cycle, namely the students were given the task in pairs to prepare a conversation with 5 dialogue questions. The results showed that learning in cycle 1 obtained results that were classified as low. Almost all students could not respond to the dialogue from the teacher. Learning in cycle 2 shows that all students can carry out conversations well, are relatively fluent and are in the assessment category, namely praise